Pembelajaran Kosakata dan Kemampuan Berbahasa Terhadap Anak Tunanetra - Agustini Br. Sinaga; Debora, Debora Siregar; Gracia Patunia Butarbutar; Laura Debrina Tarigan; May Syaroh; Zahwa Maulidina Assyifa; Lili Tansliova; Anggia Puteri (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to identify the vocabulary comprehension process and effective Indonesian language learning methods for blind children. The method used for this study is a literature study. Data were collected from various articles, books, and other relevant sources, then selected based on two main criteria, namely an explanation of the vocabulary comprehension process and Indonesian language learning methods for blind children. The results of the study show that blind children can understand vocabulary through sound associations with objects or concepts that can be felt directly through touch or motor experience. Blind children learn Indonesian by utilizing their senses that are still functioning, such as hearing and touch, children with this type of disability can develop language skills through various effective methods and media. Learning Indonesian for Children with Special Needs (ABK), one of which is blind, requires curriculum adaptation, special learning media, and teaching strategies that are adjusted to their learning characteristics.